1998
DOI: 10.1007/s005950050189
|View full text |Cite
|
Sign up to set email alerts
|

The expression of cadherin-catenin complex in association with the clinicopathologic features of early gastric cancer

Abstract: Although impaired expression of E-cadherin (E-cad) is frequently observed in tumors with aggressive histopathologic characteristics, the correlation between alpha-catenin (alpha-cat) expression and the clinicopathologic features of early gastric cancer have not been fully examined. In this study, we evaluated the expression of E-cad and alpha-cat by early gastric carcinomas, and examined the relationships between this expression and various clinicopathologic characteristics. A total of 69 specimens obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
0
12
0
2
Order By: Relevance
“…reported that reduced cancer cell expression of claudin‐7, but not claudin‐1, correlated with LNM in ESCC 14 . In the present study, the cutoff points between normal and abnormal expressions for these parameters were decided by using definitions of the previous studies 23,32–34 . Even when LNM was evaluated by using other cutoff points with the help of a receiver operating characteristic (ROC) curve, statistical significance could not be found between LNM and abnormal expressions (data not shown).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…reported that reduced cancer cell expression of claudin‐7, but not claudin‐1, correlated with LNM in ESCC 14 . In the present study, the cutoff points between normal and abnormal expressions for these parameters were decided by using definitions of the previous studies 23,32–34 . Even when LNM was evaluated by using other cutoff points with the help of a receiver operating characteristic (ROC) curve, statistical significance could not be found between LNM and abnormal expressions (data not shown).…”
Section: Discussionmentioning
confidence: 69%
“…14 In the present study, the cutoff points between normal and abnormal expressions for these parameters were decided by using definitions of the previous studies. 23,[32][33][34] Even when LNM was evaluated by using other cutoff points with the help of a receiver operating characteristic (ROC) curve, statistical significance could not be found between LNM and abnormal expressions (data not shown). All of the previous studies which reported significant correlations between LNM and abnormal expressions included many cases with invasion of the proprial muscle layers or even deeper.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical studies using surgically resected specimens have shown abnormal expression of the complex in 30±75 per cent of gastric cancers 11,14,25,33,34 . Jawhari et al 14 have reported that abnormal E-cadherin and g-catenin staining occurred more frequently in diffuse-type than intestinal-type gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have focused on the expression of these molecules in early gastric cancer 19,25,34 . However, previous assessments of E-cadherin±catenin complex immunoreactivity in early gastric cancer were based on comparisons with staining intensity of normal gastric epithelium and, in general, these studies combined intramucosal and submucosal carcinomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation